A Survey of Core Research in Information Systems - Sidorova, Anna.; Evangelopoulos, Nicholas; Torres, Russell; Johnson, Vess.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
The Information Systems (IS) discipline was founded on the intersection of computer science and organizational sciences, and produced a rich body of research on topics ranging from database design and the strategic role of IT to website design and online consumer behavior. In this book, the authors provide an introduction to the discipline, its development, and the structure of IS research, at a level that is appropriate for emerging and current IS scholars. Guided by a bibliometric study of all research articles published in eight premier IS research journals over a 20-year period, the authors identify and present the top 51 IS research topics. For each topic, they provide a brief overview, time trends, and references to related influential research works. The topics are organized into an IS research framework that includes research on the IT artifact and IS development, IT and organizations, IT and individuals, IT and markets, and IT for teamwork and collaboration.
Introduction -- The structure of IS research and IS discipline development -- IT artifact and IS development -- IT and Organizations -- IT and Individuals -- IT and Markets -- IT for Teamwork and collaboration -- Conclusion.
Keywords: Computer science; Information Systems; Computer Science; Information Systems Applications (incl. Internet).; Management of Computing and Information Systems